2017
DOI: 10.1083/jcb.201608122
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms facilitating the initial kinetochore encounter with spindle microtubules

Abstract: The initial kinetochore (KT) encounter with a spindle microtubule (MT) is one of the rate-limiting steps in establishing proper KT–MT interaction during mitosis. This study reveals how multiple factors cooperate to facilitate the KT encounter with a spindle MT. In particular, it highlights the important roles of KT-derived MTs in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…We fused BIR1 and MCM21 with the auxin-induced degron tag (bir1-aid and mcm21-aid) and investigated how this double depletion affected cell growth ( Figure 1A). STU1 is an essential gene and stu1-aid was used as a control for viability [17].…”
Section: Coma Facilitates Chromosome Bi-orientation Independently Of mentioning
confidence: 99%
“…We fused BIR1 and MCM21 with the auxin-induced degron tag (bir1-aid and mcm21-aid) and investigated how this double depletion affected cell growth ( Figure 1A). STU1 is an essential gene and stu1-aid was used as a control for viability [17].…”
Section: Coma Facilitates Chromosome Bi-orientation Independently Of mentioning
confidence: 99%
“…Table 1 lists the parameters used to solve the model. Five parameter values were taken from previous studies (Gay et al, 2012;Gonen et al, 2012;Nannas et al, 2014;O'Toole et al, 1997;Storchova et al, 2006;Vasileva et al, 2017) The other parameters are given in Figure 1C.…”
Section: Discussionmentioning
confidence: 99%
“…A microtubule that comes into the proximity of a kinetochore (KC), a protein complex at the sister chromatids, can attach to the KC and thus establish a link between chromatids and spindle poles (Akiyoshi et al, 2010;Gonen et al, 2012;Hill, 1985;Mitchison and Kirschner, 1985;Volkov et al, 2013). Theoretical studies have quantitatively shown that this process can contribute to spindle assembly (Kalinina et al, 2013;Paul et al, 2009;Vasileva et al, 2017;Wollman et al, 2005). Prior to chromosome separation, all connections between chromatids and the spindle pole must be established, and erroneous KC-microtubule attachments must be corrected for which several mechanisms are proposed (Tubman et al, 2017;Zaytsev and Grishchuk, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 ; Kitamura et al, 2007 ). The simulation was previously developed ( Gandhi et al, 2011 ; Vasileva et al, 2017 ), but several modifications were introduced in this study. The values of the majority of parameters were determined, based on previous studies ( Gandhi et al, 2011 ; Kalinina et al, 2013 ; Kitamura et al, 2007 , 2010 ; Tanaka et al, 2007 , 2005 ), and some unknown parameter values were determined in the current study ( ).…”
Section: Methodsmentioning
confidence: 99%